ANALYSIS OF ECONOMIES OF SCALE AND PRODUCTION FACTORS EFFICIENCY OF CITRUS FARMING IN KERTA VILLAGE GIANYAR REGENCY - Putu Bramanda Kusuma Yuda; Made Kembar Sri Budhi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Agriculture has an important role as one of the economic sector that supports economic development in developing countries, including Indonesia. However, the agricultural system in Indonesia has not yet reached its optimal point. The efficiency of production factors utilization is absolutely crucial for farmers. Due to this phenomenon, this study aims to analyze the simultaneous and partial influence of production factors such as land area, capital, and labor on citrus production, and to analyze the economies of scale and economic efficiency of production factors such as land area, capital, and labor in citrus farming. This study used primary data that obtained from interviews with citrus farmers in Kerta Village, Payangan District, Gianyar Regency. The sample was determined using nonprobability sampling with purposive sampling. The sample size was determined with Slovin formula, yielding a sample of 91 citrus farmers. The data analysis technique used was multiple linear regression based on the Cobb-Douglas production function. The results of this study indicate that land area, capital, and labor simultaneously had a significant influence on citrus production. Partially, the land area, capital, and labor had a positive and significant influence on citrus production. The economies of scale in citrus farming were in an increasing return to scale condition, which means that each proportional inputs increase will produce an additional output that is greater than the inputs change. The economic efficiency of the production factors utilization such as land area, capital, and labor in citrus farming was not yet efficient, so the utilization needed to be increased. These results implies the need of strategies to increase citrus production efficiency in order to increase citrus farming productivity.